Improving mental health of student and novice nurses to prevent dropout: A systematic review. (15th July 2020) - Bakker, Ellen J. M.; Kox, Jos H. A. M.; Boot, Cécile R. L.; Francke, Anneke L.; van der Beek, Allard J.; Roelofs, Pepijn D. D. M.
Abstract: Aims: To provide: (a) an overview of interventions aimed at improving mental health of student or novice nurses; and (b) an evaluation of their effectiveness on dropout‐related outcomes. Design: Systematic review. Data sources: Research papers published between January 1971–February 2019 were identified from the following databases: Embase, Medline, PsycInfo, CINAHL, ERIC, the Cochrane Library, Web of Science, and Google Scholar. Review methods: We followed the procedures recommended by the Editorial Board of the Cochrane Collaboration Back Review Group. We included peer‐reviewed articles with a quantitative research design, examining interventions aimed at improving mental health of student and novice nurses and their effect on dropout‐related outcomes. The large variation in studies prohibited statistical pooling and a synthesis without meta‐analysis of studies was performed. Results: We identified 21 studies with three areas of focus: managing stress or stressors ( N = 4); facilitating the transition to nursing practice ( N = 14); and a combined approach ( N = 3). Five studies showed a statistically significant effect on dropout‐related outcomes. The overall risk of bias was high. Conclusion: A wide range of interventions are available, but the evidence for their effectiveness is limited. There is a need for high‐quality studies in this field, preferably with a randomized controlled design. Abstract : 目的: 提供：（a）旨在改善学生或新手护士心理健康的干预措施概述；（b）评估其对辍学相关结果的有效性。 设计: 系统评估。 数据源: 1971年1月至2019年2月之间发表的研究论文来自以下数据库：Embase、Medline、PsycInfo、CINAHL、ERIC、科克伦图书馆（Cochrane Library），科学网（Web of Science）和谷歌学术（Google Scholar）。 评估方法: 我们遵循了科克伦协作回顾评述小组（Cochrane Collaboration Back Review Group）编辑委员会推荐的程序。我们纳入了具有定量研究设计的同行评审文章，研究了旨在改善学生和新手护士心理健康及其对辍学相关结果影响的干预措施。研究中的巨大差异无法进行统计汇总，采用了无荟萃分析研究的综合。 结果: 我们确定了21个研究，重点关注三个领域：管理压力或压力源（ N = 4）；促进向护理实践的过渡（ N = 14）；以及组合方法（ N = 3）。五项研究表明，与辍学相关的结果在统计上具有显著影响。总体偏倚风险很高。 结论: 干预措施的种类很多，但其有效性的证据有限。这一领域需要高质量的研究，最好采用随机对照设计。